2021
DOI: 10.3389/fcvm.2021.719603
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Significant Coronary Artery Disease Through Advanced Echocardiography: Role of Non-invasive Myocardial Work

Abstract: Background: Non-invasive prediction of critical coronary artery stenosis (CAST) in patients with coronary artery disease (CAD) is challenging. Strain parameters can often capture an impairment of regional longitudinal function; however, they are load dependent. A novel non-invasive method to estimate Myocardial Work (MW) has been recently proposed, showing a strong correlation with invasive work measurements. Our aim was to investigate the ability of non-invasive MW to predict the ischaemic risk area underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 48 publications
1
6
0
1
Order By: Relevance
“…The low specificity underlines the fact that MW should be used along with other parameters to identify patients with significant CAD. Sabatino et al [24] further extended the previous results of Edwards et al's study and found that GWI, GCW and GWE were significantly reduced in patients with critical CAD (stenosis >70%) as compared to the controls. The novelty of this study was the assessment of the regionalized MW indices.…”
Section: Chronic Coronary Syndromessupporting
confidence: 57%
“…The low specificity underlines the fact that MW should be used along with other parameters to identify patients with significant CAD. Sabatino et al [24] further extended the previous results of Edwards et al's study and found that GWI, GCW and GWE were significantly reduced in patients with critical CAD (stenosis >70%) as compared to the controls. The novelty of this study was the assessment of the regionalized MW indices.…”
Section: Chronic Coronary Syndromessupporting
confidence: 57%
“…Timing of opening and closure of the valve were manually selected from 2D echo images. Global myocardial Work Index (GWI), Global myocardial Constructive Work (GCW), Global myocardial Wasted Work (GWW), and Global myocardial Work Efficiency (GWE) were calculated as previously described [4].…”
Section: Calculation Of Non-invasive Myocardial Workmentioning
confidence: 99%
“…Left ventricular ejection fraction (LVEF) generally remains preserved despite initial deterioration of LV function. Global longitudinal strain (GLS) has been shown to be an earlier and more sensitive marker of LV dysfunction [3,4]. Nevertheless, its dependence from afterload represents a limitation in severe AS [5].…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al demonstrated that regional myocardial work measured by echocardiography exhibited a good diagnostic value in detecting significant myocardial ischaemia compared to the standard fractional flow reserve approach (measured invasively in the catheterisation laboratory) [ 58 ]. The use of regional GWE was able to identify at baseline CAD patients with critical coronary artery stenosis before invasive angiography with excellent performance (AUC = 0.92) in a trial from 2021 [ 59 ].…”
Section: Discussionmentioning
confidence: 99%